From Waste To Wealth: Pengolahan Limbah tongkol Jagung Menjadi Media Budidaya Jamur Tiram untuk mendukung Ekonomi Hijau - Mahfud Nugroho; Sufrotun Khasanah; Arbina Satria Afiatan; Fitria Yuni Astuti; Uli Maghfirotul Iza (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The high productivity of corn in Kendal Regency produces a large amount of waste that has not been optimally utilized. Therefore, appropriate technology needs to be applied to convert corn cobs into a growing medium for oyster mushrooms. Oyster mushrooms were chosen because they are among the most popular edible mushrooms in society and have relatively stable market prices, making them suitable for cultivation. The purpose of this program is to improve the knowledge and skills of the Sekandang Farmers Group in producing oyster mushroom growing media using corn cob waste. The method used in this community service activity involves both theoretical and practical training, including corn cob grinding, mixing with rice bran and lime, sterilization using a steamer machine, seeding, as well as basic financial management and marketing strategies (both online and offline). The results of the program, based on interviews and pre-test and post-test evaluations, show a significant increase in participants’ scores, indicating improved knowledge and skills among the farmers. In addition, participants demonstrated high enthusiasm and active participation during the practical sessions. In conclusion, this training successfully enhanced the farmers’ ability to utilize corn cob waste as an effective growing medium for oyster mushrooms, thereby supporting the improvement of their economic welfare.